ANALISIS PERBANDINGAN UNJUK KERJA PROTOKOL TCP DENGAN DCCP MENGGUNAKAN TRAFIK DATA BURSTY - Setiawan, Wahyu; Jusak, Jusak; Triwidyastuti, Yosefine (Journal of Control and Network Systems (JCONES), 2016)
Technological developments are very fast, especially the use of Internet technology. So many people are switching from a desktop application to a web based application function due to a more dynamic. Furthermore, it can be accessed anywhere as long as there is an internet connection.Understanding internet traffic is very useful in analizing performance of the internet services. In general there are two types of traffic pattern, they are continuous and bursty traffic. The bursty traffic shows pattern of volatile and unpredictable with sudden spikes in traffic volume.Increment of multimedia applications in the internet currently, causes the UDP traffic is widespread on the internet that could cause network congestion and threaten the TCP traffic. It mainly appears issues of fairness between the two protocols. Hence, in 2006, the IETF introduced a new protocol called Datagram Congestion Control Protocol ( DCCP ) CCID2 and CCID3.In our study, based on the test results of TCP and DCCP protocol, showed a comparison of performance test for QoS parameters and fairness which found that overall protocol TCP has better performance than protocol DCCP for bursty data traffic on packet loss and delay. On the other hand, in terms of the bandwidth utilization, it shows that network performance TCP and DCCP did not show any significant differences. Moreover in terms of fairness, it can be seen that the DCCP  protocol CCID-3 is better than the DCCP CCID-2.